Toward a multiple clock - Talpes, E.
Enabled by the continuous advancement in fabrication technology, present-day synchronous microprocessors include more than 100 million transistors and have clock speeds well in excess of the 1-GHz mark. Distributing a low-skew clock signal in this frequency range to all areas of a large chip is a task of growing complexity. As a solution to this problem, designers have recently suggested the use of frequency islands that are locally clocked and externally communicate with each other using mixed clock communication schemes. Such a design style fits nicely with the recently proposed concept of voltage islands that, in addition, can potentially enable fine-grain dynamic power management by simultaneous voltage and frequency scaling. This paper proposes a design exploration framework for application-adaptive multiple-clock processors which provides the means for analyzing and identifying the right interdomain communication scheme and the proper granularity for the choice of voltage/frequency islands in case of superscalar, out-of-order processors. In addition, the presented design exploration framework allows for comparative analysis of newly proposed or already published application-driven dynamic power management strategies. Such a design exploration framework and accompanying results can help designers and computer architects in choosing the right design strategy for achieving better power-performance tradeoffs in multiple-clock high-end processors.
Keywords: Application-adaptive multiple-clock processors; Clock signal; Clocking strategies; Comparative analysis; Design exploration; Dynamic power management; Interdomain communication; Low-power design; Multiple clock/voltage island design; Out-of-order processors; Power-aware processors; Superscalar processors; Synchronous microprocessors; Voltage/frequency islands